Mathematical Problem Solution Paths Of Trainees In A Teacher Training College - Koay, Chen Yong (2007)
This study explores the mental images of problem solving and the mathematical problem solution paths of trainee teachers in a teacher training college. The mathematical problem solution paths of successful and unsuccessful problem solvers are also identified. This research adopts a constructivist perspective that views learning mathematics as a process of constructing meaningful representation and knowledge is constructed by the individual himself or herself. This research employs the open coding techniques and the interpretative approach. Seventeen trainees majoring in mathematics undertaking the Malaysian Diploma in Teaching (KDPM) and the Post Graduate in Teaching (KPLI) courses were selected by purposive sampling. Data were collected by audio and video taping the trainee teachers while solving six tasks individually using the think-aloud technique, followed by retrospection and clinical interviews. The analysis involved the trainee teachers' solution paths and transcripts of the think-aloud problem solving sessions. The transcripts of the retrospection and clinical interviews provide the basis for triangulation to ascertain the trainee teachers' mental images of problem solving and mathematical problem solution paths. The findings of this study show that the trainee teachers have composite mental images of problem solving. The most common mental images that emerged are 'as a process', 'as a goal', and 'as an obstacle'.